2008
DOI: 10.1186/1742-2094-5-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of interleukin-1 in neuroinflammation and Alzheimer disease: an evolving perspective

Abstract: Elevation of the proinflammatory cytokine Interleukin-1 (IL-1) is an integral part of the local tissue reaction to central nervous system (CNS) insult. The discovery of increased IL-1 levels in patients following acute injury and in chronic neurodegenerative disease laid the foundation for two decades of research that has provided important details regarding IL-1's biology and function in the CNS. IL-1 elevation is now recognized as a critical component of the brain's patterned response to insults, termed neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
313
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(347 citation statements)
references
References 153 publications
12
313
1
3
Order By: Relevance
“…Exposure to Cre recombinase induces IL-1β expression, reaching peak inflammation at 14 days. [45][46][47] We further confirmed that intracranial injection of Cre recombinase-expressing lentivirus caused upregulation of a number of inflammatory markers, including IFNγ and TNFα (Figure 7d). …”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Exposure to Cre recombinase induces IL-1β expression, reaching peak inflammation at 14 days. [45][46][47] We further confirmed that intracranial injection of Cre recombinase-expressing lentivirus caused upregulation of a number of inflammatory markers, including IFNγ and TNFα (Figure 7d). …”
Section: Resultssupporting
confidence: 63%
“…IL-1β XAT mice show no overt oligodendrocyte death despite significant leukocyte infiltration into the CNS, [45][46][47] suggesting Figure 4 PKR activation is required for IFNγ-mediated oligodendrocyte protection. (a) Whole-cell lysates were obtained from oligodendrocytes treated as indicated for 72 h and probed by western blotting for PKR, phospho-eIF2α, eIF2α, phospho-PERK, PERK and β-tubulin.…”
Section: Resultsmentioning
confidence: 99%
“…Interleukin-1-beta (IL-1β), a critical component of brain neuroinflammation, is increased in AD brains 5 and may contribute to AD pathology by increasing amyloid precursor protein (APP) gene expression, Tau hyperphosphorylation and memory impairment. 6 However, antiinflammatory therapies have not provided the expected beneficial effect in AD patients, 7 suggesting that microglial inflammation may be a consequence of AD. Degenerating neurons are renowned initiators of brain inflammatory responses and the loss of synapses remains the best correlative marker of dementia in AD.…”
mentioning
confidence: 99%
“…[37][38][39] As such, IL-1a levels in brain lysates, prepared as indicated above, were measured in the non-Tg WT as well as experimental and control vaccinated a¡Syn expressing Tg mice. Data on levels of IL-1a are indicated in Figure 4 and are expressed as mean pg/ml brain lysate § SEM.…”
Section: Resultsmentioning
confidence: 99%